A Green Synthesis of Quinoxalines and 2,3-Dihydropyrazines - Delpivo, Camilla; Micheletti, Gabriele; Boga, Carla (Synthesis, 2013)
Quinoxaline and dihydropyrazine derivatives were obtained in high yields by simple addition of 1,2-diamines and 1,2-dicarbonyl compounds in water. In some cases, the products spontaneously precipitated from the reaction mixture, making it possible to recover and reuse the mother liquor for further condensations. The very mild reaction conditions, the high yields of the products, and the absence of any catalyst make this methodology an efficient and green route to quinoxalines and dihydropyrazines.
Keywords: quinoxaline; dihydropyrazine; green; water; condensation